The Implementation of Jigsaw Technique with Musical Background in Comprehending Reading Text - Ammang Latifa; Rafi’ah Nur; Muhammad Faried Wadjedy (Soegijapranata Catholic University, 2020)
This research studies the impact of the implementation of the Jigsaw technique with a musical background to comprehend reading at Senior high school in Sidrap, Indonesia. This research uses a quasi-experimental method to answer the question,